Short-term growth of octocorals Swiftia exserta and Muricea pendula in a mesocosm - Lange, Kassidy; Etnoyer, Peter (Frontiers in Marine Science, 2024)
To optimize fragmentation approaches for restoration applications, this study assessed fragmentation size influences on health and growth rates of mesophotic octocorals. Growth rates for Swiftia exserta (n=6) and Muricea pendula (n=9) were determined using photogrammetry in a mesocosm over a 90-day trial. No significant difference was found in growth between fragmented size classes (3, 6, and 12 cm) (S. exserta p=0.156, M. pendula p=0.393). There was a significant difference (p=0.013) in growth rates between species, with faster annual growth (mean ± SE) for S. exserta (1.490 ± 0.399 cm/year) than for M. pendula (0.550 ± 0.228 cm/year). Fragments from healthy source colonies remained healthy, while fragments from an unhealthy colony experienced tissue loss. Healthy colonies may successfully be used for fragmentation in laboratory propagation, though optimal fragment size for restoration remains debatable. Use of laboratory-based propagation techniques to recover injured species may require better understanding of factors influencing growth.